2012
DOI: 10.1016/s1474-4422(12)70133-3
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin 4 and neuromyelitis optica

Abstract: Neuromyelitis optica is an inflammatory demyelinating disorder of the CNS. The discovery of circulating IgG1 antibodies against the astrocyte water channel protein aquaporin 4 (AQP4) and the evidence that AQP4-IgG is involved in the development of neuromyelitis optica revolutionised our understanding of the disease. However, important unanswered questions remain—for example, we do not know the cause of AQP4-IgG-negative disease, how astrocyte damage causes demyelination, the role of T cells, why peripheral AQP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
441
0
21

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 500 publications
(469 citation statements)
references
References 106 publications
(193 reference statements)
7
441
0
21
Order By: Relevance
“…Autoreactive lymphocytes originating in the teratoma could enter the blood stream, cross the blood-brain barrier and cause the neurological disease. Alternatively AQP4 antibodies might be produced peripherally and enter the CNS secondarily (Papadopoulos and Verkman, 2012). In a recent report of a patient with paraneoplastic myelitis, breast cancer and AQP4 antibodies, the tumor was also found to express the AQP4 antigen (Armağan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Autoreactive lymphocytes originating in the teratoma could enter the blood stream, cross the blood-brain barrier and cause the neurological disease. Alternatively AQP4 antibodies might be produced peripherally and enter the CNS secondarily (Papadopoulos and Verkman, 2012). In a recent report of a patient with paraneoplastic myelitis, breast cancer and AQP4 antibodies, the tumor was also found to express the AQP4 antigen (Armağan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…NMO is a rare inflammatory demyelinating disease of the central nervous system (CNS) [1], with an estimated prevalence of 0.3-4.4/100.000 [2]. It is more prevalent in females (9:1) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Neuromyelitis optica is a rare severe inflammatory demyelinating disorder of the central nervous system, which is related to multiple sclerosis but distinctly different and manifested mainly by paralysis and optic nerve damage [177,178]. It has been conclusively demonstrated that this condition is caused by an autoimmune reaction to aquaporin-4, which is highly expressed in the astrocyte membrane [177,178].…”
Section: Neuromyelitis Optica and Aquiporinmentioning
confidence: 99%
“…It has been conclusively demonstrated that this condition is caused by an autoimmune reaction to aquaporin-4, which is highly expressed in the astrocyte membrane [177,178].…”
Section: Neuromyelitis Optica and Aquiporinmentioning
confidence: 99%